2017
DOI: 10.1021/acs.macromol.7b01639
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Crystalline Properties of 2-Isopropyl-2-oxazoline Copolymers in Condensed State and in Solution Depending on the Composition

Abstract: Copolymers of 2-isopropyl- (iPrOx) and 2-n-propyl-2-oxazoline (nPrOx) were obtained, and attempts to control their crystallization both in condensed state and in solution were made. The homopolymer of nPrOx showed a weaker crystallization tendency than PiPrOx; nevertheless, the frequently encountered assumption that it is completely amorphous and is not able to crystallize was found to be unjustified. By increasing the amount of nPrOx in copolymers, their crystallization ability decreased both in the condensed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…The glass transition of PiPrOx could be seen at a temperature of approximately 70 • C. Copolymerisation of iPrOx with nPrOx led to a considerable plasticising effect, and a decrease in T g to~50 • C was observed. These values were consistent with data from the literature [48].…”
Section: Synthesis and Characterisation Of (Co)poly(2-oxazoline)ssupporting
confidence: 93%
See 2 more Smart Citations
“…The glass transition of PiPrOx could be seen at a temperature of approximately 70 • C. Copolymerisation of iPrOx with nPrOx led to a considerable plasticising effect, and a decrease in T g to~50 • C was observed. These values were consistent with data from the literature [48].…”
Section: Synthesis and Characterisation Of (Co)poly(2-oxazoline)ssupporting
confidence: 93%
“…Although its cloud point temperature (T CP ) in aqueous solution is close to that of the human body, making it attractive for many applications, the presence of a crystalline phase is often not desirable in some systems. It was shown [48] that copolymerisation of iPrOx with n-propyl-2-oxazoline in an amount of 50 mol% significantly decreased the ability of the copolymers to crystallise, compared to the homopolymers of iPrOx. The aim of these studies was to determine whether iPrOx-based (co)polymers could be processed by electrospinning and extrusion from the melt techniques and to determine how processing affects their properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the amount of MOx in copolymers (relatively rigid monomer units compared to iPrOx) caused an anti-plasticizing effect, and a slight increase in the glass transition from 68 °C (10 mol% MOx) to 73 °C (51 mol% MOx) was observed ( Figure 1c). It is known that the amount of crystalline phase in many POxs can be increased by annealing for a prolonged time and at an elevated temperature [26,28]. To check how much the ability to crystallize iPrOx/MOx copolymers increases after the thermal treatment, the copolymers were annealed at 150 °C for 1 h and then cooled slowly to room temperature at a rate of 10 °C/min.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that by the copolymerization of 2-isopropyl-with 2-n-propyl-2-oxazoline (nPrOx) (50 mol%), it was possible to obtain gradient copolymers with a significantly lower crystallization ability than PiPrOx, with only a slight change in LCST [26]. This property was explained by the higher elasticity of nPrOx units, which disturbed the spatial arrangements of the ordered iPrOx units.…”
Section: Introductionmentioning
confidence: 99%